Analysis of Digital Television Signal Reception in Combined Transmitter Antenna Systems - Hana Fatimah Zahra; Endah Setyowati; Dewi Indriati Hadi Putri (Jurnal ELTIKOM: Jurnal Teknik Elektro, Teknologi Informasi dan Komputer)
The Indonesian broadcasting sector has undergone significant transformation with the implementation of the Analogue Switch Off (ASO) program. By July 2023, approximately 97.23% of television stations in Indonesia had migrated to digital broadcasting. However, this figure does not reflect an equitable distribution of normal broadcasts. Data from Transmission Station X indicate that 6.77% of broadcasts are blank, 12.24% experience freezing, and only 80.99% are classified as normal for channel X in the Jabodetabek region. These statistics suggest that the primary objective of the ASO program—providing an enhanced television viewing experience—has not yet been universally achieved. Therefore, efforts are required to ensure the equitable distribution of normal broadcasts. Transitioning from a lower transmitter antenna system to a combined transmitter antenna system is proposed as a potential solution. This study evaluates the Modulation Error Ratio (MER) values in the Jabodetabek region when channel X uses a combined transmitter antenna system. Measurements, conducted using the drive test method, reveal that 99.703% of MER data are above the threshold (normal broadcasts), 0.042% are at the threshold (freeze broadcasts), and 0.255% are below the threshold (blank broadcasts). These results demonstrate that adopting a combined transmitter antenna system can help address the uneven distribution of normal broadcasts in the Jabodetabek region.